Development of the ELISA Test System for Quantitative Determination of IgG to the Varizella zoster virus in Human Serum and Assessment of its Diagnostic Efficiency - L. N. Lukhverchyk; G. L. Alatortseva; L. N. Nesterenko; V. Y. Kabargina; V. V. Dotsenko; I. I. Amiantova; O. B. Vylivannaya; A. V. Sidorov; A. V. Milovanova; O. S. Oksanich; S. Y. Konanykhina; V. V. Zverev (Эпидемиология и вакцинопрофилактика)
Relevance. The introduction of Varicella vaccine prophylaxis explains the need to develop a methodology for monitoring the vaccination effectiveness and the intensity of population immunity. This problem can be solved using quantitative immunoassay methods. Aim. Development of an enzyme-linked immunosorbent assay for the concentration of class G immunoglobulins (AB) to Varicella zoster virus (VZV) determining and assessing its functional characteristics and diagnostic efficiency. Materials and methods. Recombinant antigen GE VZV. WHO International Standard for Antibodies to VZV W1044. Blood serum samples from healthy people and patients with Chickenpox and Herpes zoster, blood serum samples containing IgG antibodies to herpes simplex viruses of the first and second types, cytomegalovirus, Epstein-Barr virus. Anti-VZV ELISA (IgG) reagent kit (Euroimmun, Germany). Indirect enzyme-linked immunosorbent assay. Immunization of animals with recombinant antigen GE, isolation, and purification of specific antibodies. Conjugation of monoclonal antibodies to human IgG with antibodies to antigen GE and with horseradish peroxidase. Results. An enzyme-linked immunosorbent assay in «an indirect» format has been developed to determine the specific antibodies to VZV concentration (IU/ml) in human serum/plasma. An artificial calibrator for determining the concentration of AB-VZV had been synthesized and standardized according to the International WHO-standard W1044. The main functional characteristics of the developed enzyme-linked immunosorbent assay are determined in accordance with GOST 51352-2013. The diagnostic kit was tested on blood serum samples from children with chickenpox (n = 43), adults with Herpes zoster (n = 158), healthy individuals (n = 781). The diagnostic sensitivity of the test system was 85%, the diagnostic specificity was 87% according to the ROC analysis. The absence of cross-reactivity of the test system was shown on samples with serological markers of other herpesvirus infections (n = 94). Comparative trials of the developed test system and its commercial analog, the Anti-VZV ELISA (IgG) reagent kit, did not reveal statistically significant differences between their functional characteristics. Conclusions. The developed test system for determining of the AB-VZV concentration in human serum/plasma in terms of its functional characteristics meets the GOST requirements, is characterized by high diagnostic efficiency, can be used to monitor the effectiveness of vaccine prophylaxis and strength of population immunity, as well as to assess the immune response in chickenpox and Herpes zoster.